Effects of combined application of nitrogen, phosphorus, and potassium fertilizers on seed yield, seed quality and economic returns of Elymus nutans in alpine region - Jianchao Song; Hang Yang; Xiaojun Yu; Yanzhu Chen; Caiyan Yang; Youlong He; Haibo Wang (BMC Plant Biology)
Abstract The Qinghai-Tibetan Plateau (QTP), one of the most important ecological regions in the world, is experiencing a decline in ecological function as a result of severe grassland degradation. Elymus nutans is one of the ecological grass species for restoring degraded grasslands in QTP. The seed yield and seed quality are often limited by soil nutrients in QTP, so it is very important to optimize the application rates of fertilizer for E. nutans seed production. In this study, a “3414” fertilization experiment (nitrogen: 0 ~ 225 kg N ha− 1; phosphorus: 0 ~ 180 kg P2O5 ha− 1; potassium: 0 ~ 135 kg K2O ha− 1) was established in the third year of planting E. nutans seed field based on the soil nutrient supply situation in the planting area to explore the effects of combined application of N, P and K fertilizers on the seed yield and seed quality of E. nutans. The results showed that the balanced application of N, P and K fertilizers significantly improved the seed yield, seed quality and seed vigour of E. nutans. The seed yield of E. nutans was regulated by the seed yield components. Under different fertilization treatments, the number of fertile tillers and thousand kernel weight had a greater contribution to seed yield, followed by the number of spikelets per panicle. Compared to the no fertilization treatment, the combined application of N, P, and K fertilizers increased the seed yield of E. nutans by 23.05%–90.49%. The seed size, seed nutrient content, germination percentage and seedling growth of E. nutans were positively affected by the combined application of N, P and K fertilizers. The seed vigour of E. nutans increased by 38.23%–89.85% compared to the no fertilizer treatment. Fertilizer application promoted seed nutrient storage and increased seed size thereby promoting seed germination and seedling growth. The crude protein, soluble sugar and starch content of E. nutans seed increased by 9.70%–54.05%, 6.70%–25.70% and 4.31%–35.88%, respectively. Nitrogen fertilizer had a greater effect on seed yield and seed quality of E. nutans than phosphorus and potassium fertilizers. The balanced nitrogen, phosphorus and potassium fertilizers at an application rate of 150 kg N ha− 1, 120 kg P2O5 ha− 1, 90 kg K2O ha− 1 in the planting area of QTP was found to be the optimum fertilization amount for increasing seed yield, seed quality and net income. This study provides theoretical evidence and certain practical suggestions for sustainable forage seed production in alpine regions of QTP.